2009
DOI: 10.3945/jn.108.102079
|View full text |Cite
|
Sign up to set email alerts
|

High-Milk Supplementation with Healthy Diet Counseling Does not Affect Weight Loss but Ameliorates Insulin Action Compared with Low-Milk Supplementation in Overweight Children

Abstract: Milk consumption has decreased in children over the past years. This may play a role in the prevalence of pediatric obesity, because clinical studies have found a beneficial effect of milk consumption for weight management. The objectives of this study were to test whether high-milk consumption leads to greater weight loss and improvements in metabolic risk factors than low milk consumption during a 16-wk healthy eating diet. Overweight children aged 8-10 y were randomized to either high (4 x 236 mL/d) or low … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
36
1
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 36 publications
4
36
1
1
Order By: Relevance
“…Chan et al [9] reported that, when 50 children with low calcium intake (<800 mg daily) were allocated to either a dairy-supplemented group or a control group for 6 months, children in the control group gained body fat during the study, while children in the dairy group had no significant change in body fat. On the other hand, in a randomized controlled trial that evaluated whether high milk (4 servings/day) consumption leads to greater weight loss in overweight children than low milk (1 serving/day) consumption during the course of a 16-week healthy-eating diet, St-Onge et al [48] observed no significant differences between the groups in weight loss. Numerous intervention trials have been conducted in adults, and their findings are also conflicting.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Chan et al [9] reported that, when 50 children with low calcium intake (<800 mg daily) were allocated to either a dairy-supplemented group or a control group for 6 months, children in the control group gained body fat during the study, while children in the dairy group had no significant change in body fat. On the other hand, in a randomized controlled trial that evaluated whether high milk (4 servings/day) consumption leads to greater weight loss in overweight children than low milk (1 serving/day) consumption during the course of a 16-week healthy-eating diet, St-Onge et al [48] observed no significant differences between the groups in weight loss. Numerous intervention trials have been conducted in adults, and their findings are also conflicting.…”
Section: Discussionmentioning
confidence: 99%
“…In the literature, the majority of studies have examined milk intake, while only a few have used other dairy foods as the exposure variable. The weight of evidence suggests that milk intake is more likely to be associated with beneficial weight and body fat outcome [1,26,28,38,48], while a very small number of studies, conducted only with adults, have shown the beneficial effects of such other DPs as yogurt and cheese [3,46,56].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the lack of association observed between CMRS and cheese may be, in part, explained by the higher fat, sodium, and lower potassium held by cheese compared with milk and other fluid dairy food [38]. On the other hand, the preponderance of evidence, mostly in adults, indicates that milk intake is more likely to be associated with beneficial cardiometabolic outcomes [13], [39], [40] and [41]. Few studies have shown the beneficial effects of other dairy products [10], [36] and [42].…”
Section: Discussionmentioning
confidence: 99%
“…Ser på effekten av automater i forhold til spisevaner Pelsser et al 2009 Behandling av barn med ADHD Ser på forskjeller i selvvurdert helse blant ungdommer Robinson-O'Brien et al 2010 Ingen relevante utfall (laering eller helse), sammenheng mellom å spise det ene og det andre... Rogers et al 2010 Ser på sammenheng mellom kosthold i barndom og sykdom/ikke skolemat, ikke skolesetting Ruottinen et al 2010 Ser på naeringsinnhold og effekten av det Tiltak: Bevisstgjøring og opplaering Singhal et al 2010 Tiltak er bevisstgjøring, ikke mattilbud St-Onge et al 2009 Ser på helseutfall i forhold til omlegging av diett hos barn. Story et al 2006 Vurdering av politikkutforming Suarez-Balcazar et al 2007 Systemendringer i skolen Ser ikke på relevante utfall Wojcicki and Heyman 2006 Vurderer utfall av politikk Omhandler Kina.…”
Section: Studieunclassified